The influence of service quality and marketing mix on customer loyalty through the intervening role of customer trust and customer satisfaction in the shipping business in Indonesia - Surapati, Untung; Suharno, Suharno; Hariadi, Sugeng; Achmad, Gusti Noorlitaria (Edelweiss Applied Science and Technology, 2025)
This study examines the influence of service quality and marketing mix on customer loyalty through the mediating roles of customer trust and customer satisfaction in the Indonesian shipping industry. Utilizing a sample of 250 respondents from the Indonesian Shipbuilding and Offshore Industries Association (IPERINDO), the results reveal significant relationships among the variables. Service quality positively affects customer satisfaction (t = 3.595, p < 0.05, β = 0.129), while the marketing mix influences customer trust (t = 8.228, p < 0.05, β = 0.694). The structural model demonstrates strong predictive relevance (Q² = 99.4%), explaining 85.3% of the variation in customer loyalty. The findings underscore the importance of implementing consistent service quality and strategic marketing efforts to foster trust and satisfaction, which, in turn, enhance customer loyalty. This research contributes to understanding how customer trust and satisfaction mediate the impacts of service quality and marketing mix on customer loyalty, providing practical insights for the maritime business sector.